Low-cost composite metal catalyst and industrial synthesis method of 1, 12-dodecanediol
By using CuO/ZnO/Al2O3 composite catalyst prepared with cheap metal elements, catalyzing the hydrogenation reaction under mild conditions, solving the high energy consumption, expensive catalyst and reaction conditions of the synthesis of 1,12-dodecanediol in the prior art. The harsh problem has achieved high yield and low cost industrial synthesis.
Patent Information
- Application Number
- CN202411598927.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art has high energy consumption during the synthesis of 1,12-dodecanediol, high energy consumption during the reaction process, expensive catalysts, and harsh reaction conditions, making it difficult to achieve industrial production.
Highly active CuO/ZnO/Al2O3 composite metal catalysts were prepared by cheap and easy-to-get metal elements, and 1,12-dodecanediol was prepared under mild conditions by catalytic hydrogenation reaction.
High yield and low cost 1,12-dodecanediol synthesis is achieved, reducing reaction energy consumption and improving the economic benefits and safety of the process.
Smart Images

Figure CN119455955A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of organic synthesis, and in particular to a low-cost composite metal catalyst prepared by using cheap metals and an industrial synthesis method for preparing 1,12-dodecanediol by catalytic hydrogenolysis of 1,12-dodecanedioic acid dimethyl ester using the catalyst. Background Art
[0002] 1,12-Dodecanediol is a long-chain diol that plays an important role in the national economy. With the development of my country's economy and the continuous improvement of people's living standards, its demand continues to grow. 1,12-Dodecanediol is mainly used in pharmaceutical synthesis, high-end cosmetics manufacturing, advanced coatings, lubricants and surfactants. It is a white solid at room temperature, with a melting point of 80-82°C, a boiling point of 189°C / 12mmHg, a density of 0.9216g / ml (25°C), a molecular weight of 202.33, insoluble in water, non-toxic, environmentally friendly and has good chemical stability. At present, it is difficult to synthesize and expensive.
[0003] According to the research on the prior art, it is very difficult to prepare alcohol from carboxylic acid, which requires high temperature and high pressure conditions. For example, patent application CN103449971A records that 1,12-dodecanedioic acid is catalytically hydrogenated at 18MPa and 240°C using a composite catalyst of precious metals palladium, platinum and ruthenium under ultrasonic conditions to produce 1,12-dodecanediol. The process conditions are harsh, and the metal elements in the catalyst are all precious metals, which are rare and difficult to obtain and expensive. The product yield is only 73%, which has a low yield and high cost, and the overall economic benefit of the process is poor. Using ester reduction to prepare alcohol is another idea, such as Angew.Chem.Int.Ed.(2018), 57(28), 8775-8779, mentioning that 1,12-dodecane dioic acid dimethyl ester is reduced with lithium aluminum hydride to prepare 1,12-dodecane diol, and the yield of the process can reach 94%, but lithium aluminum hydride chemical reduction needs to be operated under harsh anhydrous and oxygen-free conditions, and its conditions are more harsh, the reaction process is flammable and explosive, and a large amount of aluminate wastewater will be produced, which is difficult to achieve industrial production, and even the laboratory single kettle operation amount is not allowed to exceed 25g. Based on this reason, the industrial application of the method is greatly limited, and the method can only stay in the micro-experimental stage of the laboratory at present. It can be seen that there is currently a lack of a low-cost, easy-to-control, good safety of the synthesis process, and high yield of industrial synthesis methods. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a low-cost composite metal catalyst and an industrial synthesis method for 1,12-dodecanediol, wherein a high-activity CuO / ZnO / Al2O3 composite metal catalyst is prepared by using cheap metals. The catalyst can use cheap and readily available 1,12-dodecanedioic acid dimethyl ester as a raw material, and catalytically hydrogenate to prepare 1,12-dodecanediol under milder conditions than the prior art, so that high yield and low cost can be achieved under the premise of greatly reducing the difficulty of controlling process conditions and improving process safety, thereby solving the technical problems of high energy consumption, expensive catalysts, harsh reaction conditions and difficulty in realizing industrial production in the reaction process of synthesizing 1,12-dodecanediol in the prior art.
[0006] (II) Technical solution
[0007] In the first aspect, the present invention provides a low-cost composite metal catalyst, which is a CuO / ZnO / Al2O3 composite metal catalyst, wherein the molar ratio of CuO, ZnO and Al2O3 is 6-4:3-4:0.5-1; the composite catalyst is prepared by adding carbonate to a mixed brine solution of copper salt, zinc salt and aluminum salt for co-precipitation, grinding the filter cake and then high-temperature calcination.
[0008] According to a preferred embodiment of the present invention, the preparation method of the composite metal catalyst is as follows: preparing a mixed salt solution containing copper salt, zinc salt and aluminum salt, and gradually adding a carbonate solution to the mixed salt solution, wherein the ratio of the molar amount of carbonate to the total molar amount of copper ions, zinc ions and aluminum ions is 1 to 1.1:1 (so that the carbonate is slightly sufficient or slightly excessive);
[0009] During the dropping process, the reaction system is continuously stirred and maintained at a pH of 7-7.4; the temperature is 70-75°C; after the dropping is completed, a suspension is obtained, the suspension is heated to 80-85°C, aged for 30-40 minutes, and then the precipitate is filtered out, and the filter cake is washed with deionized water; the washed filter cake is dried, ground, and passed through a 40-60 mesh sieve to obtain a powder, and the powder is roasted at 350-550°C for 4-6 hours to obtain the composite metal catalyst.
[0010] According to a preferred embodiment of the present invention, during the dropwise addition, the pH of the reaction system is continuously stirred and maintained at 7; the temperature is 70°C, and after the dropwise addition is completed, a suspension is obtained, the suspension is heated to 80°C, aged for 30 minutes, and then the precipitate is filtered out, and the filter cake is washed with deionized water; the washed filter cake is dried, ground, and passed through a 40-mesh sieve to obtain a powder, and the powder is calcined at 350°C for 5 hours to obtain the composite metal catalyst. The drying process is air drying at 80°C for 12 hours.
[0011] According to a preferred embodiment of the present invention, the copper salt, the zinc salt and the aluminum salt are respectively copper nitrate, zinc nitrate and aluminum nitrate; the preparation process is: according to the stoichiometric ratio of each element of the composite metal catalyst, Cu(NO3)2.3H2O, Zn(NO3)2.6H2O, Al(NO3)3.9H2O are weighed and dissolved in deionized water to obtain the mixed brine solution.
[0012] According to a preferred embodiment of the present invention, the carbonate is sodium carbonate.
[0013] Preferably, in the mixed brine solution, the molar ratio of copper salt, zinc salt and aluminum salt is 6:3:1, that is, 0.6 mol of Cu(NO3)2.3H2O, 0.3 mol of Zn(NO3)2.6H2O and 0.1 mol of Al(NO3)3.9H2O are weighed, and the molar ratio of CuO, ZnO and Al2O3 in the finally prepared CuO / ZnO / Al2O3 composite metal catalyst is 6:3:0.5; or 0.4 mol of Cu(NO3)2.3H2O, 0.4 mol of Zn(NO3)2.6H2O and 0.2 mol of Al(NO3)3.9H2O are weighed, and the molar ratio of CuO, ZnO and Al2O3 in the finally prepared CuO / ZnO / Al2O3 composite metal catalyst is 4:4:1.
[0014] In a second aspect, the present invention provides an industrial synthesis method of 1,12-dodecanediol, comprising:
[0015] (1) putting 1,12-dodecanedioic acid dimethyl ester into a reaction kettle containing ethanol, adding the composite metal catalyst accounting for 4.5-6% of the mass of 1,12-dodecanedioic acid dimethyl ester, and dispersing the catalyst uniformly;
[0016] (2) introducing nitrogen or argon to evacuate and deoxygenate the reactor, then introducing hydrogen to make the pressure in the reactor reach 6.0-6.2 MPa, raising the temperature to 200-250° C. under stirring to carry out hydrogenolysis reaction, continuously introducing hydrogen during the reaction, controlling the reaction pressure to rise to a maximum of 8.3 MPa-12 MPa, and completing the reaction for 4.5-6 hours;
[0017] (3) After the reaction is completed, the reaction mixture is filtered and the filter cake is rinsed with ethanol. The solid obtained is the recovered catalyst. The filtrate obtained by filtration is evaporated under reduced pressure to remove the solvent, and the filtrate is distilled under reduced pressure to collect the 166-168°C / 4 mmHg fraction to obtain a white solid, which is 1,12-dodecanediol.
[0018] According to a preferred embodiment of the present invention, the recovered catalyst is further subjected to regeneration treatment, wherein the treatment process comprises: washing the obtained solid with dilute hydrochloric acid, dilute sodium hydroxide solution, deionized water, ethanol, and deionized water ultrasonically in sequence, drying after washing, grinding, passing through a 40-60 mesh sieve to obtain a powder, and calcining the powder at 350-550° C. for 4-6 hours to complete the regeneration of the catalyst. The regenerated catalyst can be used in the next batch of synthesis processes.
[0019] The drying process is air drying at 80° C. for 12 hours.
[0020] Preferably, the process of regenerating the recovered catalyst includes: ultrasonically washing the obtained solid with 5% hydrochloric acid, 5% sodium hydroxide solution, deionized water, ethanol, and deionized water in sequence, drying after washing (drying with air at 80°C for 12 hours), grinding, passing through a 40-mesh sieve to obtain a powder, and calcining the powder at 350°C for 5 hours to complete the regeneration of the catalyst.
[0021] (III) Beneficial effects
[0022] The technical effects of the present invention include the following aspects:
[0023] (1) The present invention uses cheap and readily available metal elements to prepare a highly active CuO / ZnO / Al2O3 composite metal catalyst. Compared with precious metal composite catalysts such as Pd / Pt / Ru, the catalyst raw materials of the present invention are easily available, the preparation cost is low, the catalyst activity is high, and the industrial economic benefits are better.
[0024] (2) The present invention uses a CuO / ZnO / Al2O3 composite metal catalyst to prepare 1,12-dodecanediol by catalytic hydrogenation using cheap and readily available 1,12-dodecane dioic acid dimethyl ester as a raw material. The process can be smoothly carried out at a pressure of about 8 MPa and a temperature of about 200°C. The reaction process is simple, the conditions are mild, the control difficulty is small, and the process stability is high. Compared with the conditions of "18 MPa, 240°C" in the prior art, the reaction energy consumption can be greatly reduced.
[0025] (3) The 1,12-dodecanediol synthesis method of the present invention has good safety in the synthesis process, no flammable and explosive intermediates are produced, the catalyst is recovered and reused, the synthesis process does not require post-treatment such as acid-base neutralization, has low corrosion to equipment, no three wastes are discharged, is safer and more environmentally friendly, has good environmental performance, and has good prospects for industrial application.
[0026] (4) The 1,12-dodecanediol synthesis method of the present invention has a product yield of more than 90%. It is an industrial synthesis method with low overall process cost, controllable temperature conditions, good safety of the synthesis process, and high yield. The product has high purity and is more competitive in the market. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is the chemical reaction formula of the synthesis method of 1,12-dodecanediol of the present invention.
[0028] Figure 2 This is the GC analysis spectrum of the product prepared in Example 1.
[0029] Figure 3 This is the FTIR spectrum of the product prepared in Example 1. DETAILED DESCRIPTION
[0030] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through implementation modes in conjunction with the accompanying drawings.
[0031] Example 1
[0032] This embodiment provides an industrial synthesis method of 1,12-dodecanediol, which comprises:
[0033] (1) Preparation of CuO / ZnO / Al2O3 composite catalyst
[0034] Add 100 mL of deionized water to a 2-liter four-necked round-bottom flask equipped with a mechanical stirrer, a thermometer, and a constant pressure dropping funnel, raise the temperature to 70°C, and dropwise add 0.6 mol of Cu(NO3)2.3H2O, 0.3 mol of Zn(NO3)2.6H2O, 0.1 mol of a mixed salt solution of Al(NO3)3.9H2O (volume 1L), and 1.0 mol of a solution of Na2CO3 (volume 1L) while stirring. During the dropping process, keep the pH at 7 and the temperature at 70°C. After the dropping is completed, heat the suspension to 80°C, age for 30 minutes, filter out the precipitate, and wash the filter cake with deionized water. The washed filter cake was dried at 80°C for 12 hours, ground, and passed through a 40-mesh sieve. The resulting material was calcined in a muffle furnace at 350°C for 5 hours to obtain 75.2 g of Cu / Zn=2:1 (molar ratio) CuO / ZnO / Al2O3 composite catalyst.
[0035] (2) In a 1L autoclave, 0.1 mol of 1,12-dodecane dioic acid dimethyl ester (25.8 g), 155 mL of ethanol, and 1.29 g (5% of the mass of 1,12-dodecane dioic acid dimethyl ester) of CuO / ZnO / Al2O3 composite catalyst were added. The air in the autoclave was replaced with N2 five times, and then H2 was introduced to 6.0 MPa. The temperature was raised to 200°C while stirring, and the reaction pressure was controlled to rise to a maximum of 8.5 MPa. The hydrogenolysis reaction was carried out for 5 hours. During the hydrogenolysis process, the following occurred: Figure 1The reaction process is shown. After the reaction is completed, the filter cake is rinsed with ethanol, and the solid is washed with 5% hydrochloric acid, 5% sodium hydroxide, deionized water, ethanol, and deionized water ultrasonically in turn, dried at 80°C for 12 hours, ground, and passed through a 40-mesh sieve. The resulting material is calcined at 350°C in a muffle furnace for 5 hours. The catalyst is regenerated and applied; the filtrate is decompressed and the solvent is removed, and then vacuum distillation is performed to collect the 166-168°C / 4mmHg fraction to obtain 18.35g of a white solid. GC analysis (such as Figure 2 ) and FTIR analysis (as shown Figure 3 The product was confirmed to be 1,12-dodecanediol, with a purity of 99.61% and a yield of 90.70%.
[0036] Example 2
[0037] This embodiment provides an industrial synthesis method of 1,12-dodecanediol, which comprises:
[0038] Into a 1L autoclave, 25.8g (0.1mol) of 1,12-dodecanediolic acid dimethyl ester, 155mL of ethanol, and 1.29g (5%) of the composite catalyst recovered and regenerated in Example 1 were added, and the air in the autoclave was replaced with N2 five times. Then, H2 was introduced to 6.0MPa, with a hydrogen-to-ester ratio of 20 / 1. The temperature was raised to 250°C with stirring, and the maximum pressure was controlled not to exceed 8.3MPa. The hydrogenolysis reaction was carried out for 5 hours. After the reaction is completed, the reaction mixture is filtered and the filter cake is rinsed with ethanol. The solid obtained is ultrasonically washed with 5% hydrochloric acid, 5% sodium hydroxide, deionized water, ethanol, and deionized water in sequence, dried at 80°C for 12 hours, ground, and passed through a 40-mesh sieve. The obtained material is calcined at 350°C in a muffle furnace for 5 hours. The catalyst is regenerated and applied again. The filtrate is decompressed and the solvent is removed by vacuum distillation. The 166-168°C / 4mmHg fraction is collected to obtain 17.46 g of a white solid. GC analysis shows that the purity is 99.15% and the yield is 86.31%.
[0039] Example 3
[0040] This embodiment provides an industrial synthesis method of 1,12-dodecanediol, which comprises:
[0041] (1) Preparation of CuO / ZnO / Al2O3 composite catalyst
[0042] Add 100 mL of deionized water to a 2-liter four-necked round-bottom flask with mechanical stirring, a thermometer, and a constant pressure dropping funnel, raise the temperature to 70°C, and dropwise add 0.6 mol of Cu(NO3)2.3H2O, 0.3 mol of Zn(NO3)2.6H2O, 0.1 mol of Al(NO3)3.9H2O mixed salt solution (volume 1L) and 1.1 mol of Na2CO3 solution (volume 1L) while stirring. During the dropwise addition, keep pH=7.3 and the temperature at 72°C. After the dropwise addition is completed, heat the suspension to 82°C, age for 40 minutes, filter out the precipitate, and wash the filter cake with deionized water. The washed filter cake was dried at 80°C for 12 hours, ground, and passed through a 40-mesh sieve. The resulting material was calcined in a muffle furnace at 350°C for 5 hours to obtain 74.4 g Cu / Zn=2:1 (molar ratio) CuO / ZnO / Al2O3 composite catalyst.
[0043] (2) In a 1-L autoclave, add 0.1 mol of 1,12-dodecanedioic acid dimethyl ester (25.8 g), 155 mL of ethanol, and 1.29 g (5% of the mass of 1,12-dodecanedioic acid dimethyl ester) of CuO / ZnO / Al2O3 composite catalyst. Replace the air in the autoclave with N2 five times, then pass H2 to 6.2 MPa, raise the temperature to 250°C while stirring, control the reaction pressure to a maximum of 10.6 MPa, and carry out the hydrogenolysis reaction for 5 h. After the reaction is completed, the reaction mixture is filtered and the filter cake is rinsed with ethanol. The solid is ultrasonically washed with 5% hydrochloric acid, 5% sodium hydroxide, deionized water, ethanol, and deionized water in sequence, dried at 80°C for 12 hours, ground, and passed through a 40-mesh sieve. The resulting material is calcined at 350°C in a muffle furnace for 5 hours. The catalyst is regenerated and applied. The filtrate is decompressed and the solvent is removed by vacuum distillation. The 166-168°C / 4mmHg fraction is collected to obtain 18.91 g of a white solid. GC analysis shows that the purity is 99.52% and the yield is 93.48%.
[0044] Example 4
[0045] This embodiment provides an industrial synthesis method of 1,12-dodecanediol, which comprises:
[0046] Into a 1L autoclave, 0.1 mol of 1,12-dodecanedioic acid dimethyl ester (25.8 g), 155 mL of ethanol, and 1.29 g (5% of the mass of 1,12-dodecanedioic acid dimethyl ester) of the composite catalyst recovered and regenerated in Example 3 were added. The air in the autoclave was replaced with N2 five times, and then H2 was passed to 6.0 MPa. The temperature was raised to 200°C while stirring, and the reaction pressure was controlled to rise to a maximum of 9.4 MPa, and the hydrogenolysis reaction was carried out for 5 hours. After the reaction is completed, the reaction mixture is filtered and the filter cake is rinsed with ethanol. The solid obtained is ultrasonically washed with 5% hydrochloric acid, 5% sodium hydroxide, deionized water, ethanol, and deionized water in sequence, dried at 80°C for 12 hours, ground, and passed through a 40-mesh sieve. The obtained material is calcined at 350°C in a muffle furnace for 5 hours. The catalyst is regenerated and applied again. The filtrate is decompressed and the solvent is removed by vacuum distillation. The 166-168°C / 4mmHg fraction is collected to obtain 18.13 g of a white solid. GC analysis shows that the purity is 99.09% and the yield is 89.61%.
[0047] Example 5
[0048] This embodiment provides an industrial synthesis method of 1,12-dodecanediol, which comprises:
[0049] (1) Preparation of CuO / ZnO / Al2O3 composite catalyst
[0050] Add 100 mL of deionized water to a 2-liter four-necked round-bottom flask with mechanical stirring, a thermometer, and a constant pressure dropping funnel, raise the temperature to 70°C, and dropwise add 0.4 mol of Cu(NO3)2.3H2O, 0.4 mol of Zn(NO3)2.6H2O, 0.2 mol of Al(NO3)3.9H2O mixed salt solution (volume 1L) and 1.0 mol of Na2CO3 solution (volume 1L) while stirring. During the dropwise addition, keep pH=7.0 and the temperature at 70°C. After the dropwise addition is completed, heat the suspension to 80°C, age for 30 minutes, filter out the precipitate, and wash the filter cake with deionized water. The washed filter cake was dried at 80°C for 12 hours, ground, and passed through a 40-mesh sieve. The resulting material was calcined in a muffle furnace at 350°C for 5 hours to obtain 71.3 g of Cu / Zn=1:1 (molar ratio) CuO / ZnO / Al2O3 composite catalyst.
[0051] (2) In a 1 L autoclave, 25.8 g (0.1 mol) of 1,12-dodecane dimethyl ester, 155 mL of methanol, and 1.29 g (5% by mass of 1,12-dodecane dimethyl ester) of the catalyst prepared in step 1 were added. The air in the autoclave was replaced with N2 five times, and then H2 was introduced to 6.0 MPa. The temperature was raised to 200° C. while stirring, and the reaction pressure was controlled to rise to a maximum of 9.4 MPa. The hydrogenolysis reaction was carried out for 5 hours. After the reaction is completed, the reaction mixture is filtered and the filter cake is rinsed with methanol. The solid obtained is ultrasonically washed with 5% hydrochloric acid, 5% sodium hydroxide, deionized water, methanol, and deionized water in sequence, dried at 80°C for 12 hours, ground, and passed through a 40-mesh sieve. The obtained material is calcined at 350°C in a muffle furnace for 5 hours. The catalyst is regenerated and applied again. The filtrate is decompressed and the solvent is removed by vacuum distillation. The 166-168°C / 4mmHg fraction is collected to obtain 17.06 g of a white solid. GC analysis shows that the purity is 99.84% and the yield is 84.33%.
[0052] Example 6
[0053] The present embodiment provides an industrial synthesis method of 1,12-dodecanediol, which comprises: adding 25.8 g (0.1 mol) of 1,12-dodecanediolatoic acid dimethyl ester, 155 mL of methanol, and 1.29 g (5%) of the composite catalyst recovered and regenerated in Example 5 into a 1 L autoclave, replacing the air in the autoclave with N2 for 5 times, then passing H2 to 6.0 MPa, heating to 250° C. under stirring, controlling the reaction pressure to a maximum of 12.0 MPa, and conducting a hydrogenolysis reaction for 5 hours. After the reaction is completed, the reaction mixture is filtered and the filter cake is rinsed with methanol. The solid obtained is sequentially ultrasonically washed with 5% hydrochloric acid, 5% sodium hydroxide, deionized water, methanol, and deionized water, dried at 80°C for 12 hours, ground, and passed through a 40-mesh sieve. The obtained material is calcined at 350°C in a muffle furnace for 5.5 hours. The catalyst is regenerated and applied again. The filtrate is decompressed and the solvent is removed by vacuum distillation. The 166-168°C / 4mmHg fraction is collected to obtain 16.55 g of a white solid. GC analysis shows that the purity is 99.22% and the yield is 81.81%.
[0054] By comparing Examples 5-6 with other examples, it was found that among the CuO / ZnO / Al2O3 composite catalysts, the catalyst with a molar ratio of CuO, ZnO and Al2O3 of 6:3:0.5 had a higher catalytic efficiency than the composite catalyst with a molar ratio of CuO, ZnO and Al2O3 of 4:4:1. In Example 6, simply increasing the hydrogenolysis reaction pressure and reaction temperature did not improve the yield relative to other examples.
[0055] Example 7
[0056] This embodiment provides an industrial synthesis method of 1,12-dodecanediol, which comprises:
[0057] (1) Preparation of CuO / ZnO / Al2O3 composite catalyst
[0058] Add 100 mL of deionized water to a 2-liter four-necked round-bottom flask equipped with a mechanical stirrer, a thermometer, and a constant pressure dropping funnel, raise the temperature to 70°C, and dropwise add 0.6 mol of Cu(NO3)2.3H2O, 0.3 mol of Zn(NO3)2.6H2O, 0.1 mol of a mixed salt solution of Al(NO3)3.9H2O (volume 1L), and 1.0 mol of a solution of Na2CO3 (volume 1L) while stirring. During the dropwise addition, keep the pH at 7.2 and the temperature at 75°C. After the dropwise addition is completed, heat the suspension to 85°C, age for 30 minutes, filter out the precipitate, and wash the filter cake with deionized water. The washed filter cake was dried at 80°C for 12 hours, ground, and passed through a 40-mesh sieve. The resulting material was calcined in a muffle furnace at 450°C for 5 hours to obtain 73.5 g of Cu / Zn=2:1 (molar ratio) CuO / ZnO / Al2O3 composite catalyst.
[0059] (2) Into a 1L autoclave, 25.8g (0.1mol) of 1,12-dodecanediolatoic acid dimethyl ester, 155mL of ethanol, and 1.29g (5%) of the composite catalyst prepared in step 1 were added, the air in the autoclave was replaced with N2 five times, and then H2 was introduced to 6.0MPa. The temperature was raised to 200°C while stirring, and the reaction pressure was controlled to rise to a maximum of 8.5MPa, and the hydrogenolysis reaction was carried out for 5 hours. After the reaction is completed, the reaction mixture is filtered and the filter cake is rinsed with ethanol. The solid obtained is sequentially ultrasonically washed with 5% hydrochloric acid, 5% sodium hydroxide, deionized water, ethanol, and deionized water, dried at 80°C for 12 hours, ground, and passed through a 40-mesh sieve. The obtained material is calcined at 350°C in a muffle furnace for 5 hours. The catalyst is regenerated and applied again. The filtrate is decompressed and the solvent is removed by vacuum distillation. The 166-168°C / 4mmHg fraction is collected to obtain 18.56 g of a white solid. GC analysis shows that the purity is 99.51% and the yield is 91.74%.
[0060] Example 8
[0061] This embodiment provides an industrial synthesis method of 1,12-dodecanediol, which comprises:
[0062] (1) Preparation of CuO / ZnO / Al2O3 composite catalyst
[0063] Add 100 mL of deionized water to a 2-liter four-necked round-bottom flask with mechanical stirring, a thermometer, and a constant pressure dropping funnel, raise the temperature to 70°C, and dropwise add 0.6 mol of Cu(NO3)2.3H2O, 0.3 mol of Zn(NO3)2.6H2O, 0.1 mol of Al(NO3)3.9H2O mixed salt solution (volume 1L) and 1.0 mol of Na2CO3 solution (volume 1L) while stirring. During the dropwise addition, keep pH=7.3 and the temperature at 75°C. After the dropwise addition is completed, heat the suspension to 80°C, age for 30 minutes, filter out the precipitate, and wash the filter cake with deionized water. The washed filter cake was dried at 80°C for 12 hours, ground, and passed through a 40-mesh sieve. The resulting material was calcined in a muffle furnace at 550°C for 5 hours to obtain 71.4 g of Cu / Zn=2:1 (molar ratio) CuO / ZnO / Al2O3 composite catalyst.
[0064] (2) Into a 1L autoclave, 25.8g (0.1mol) of 1,12-dodecanediolatoic acid dimethyl ester, 155mL of ethanol, and 1.29g (5%) of the composite catalyst prepared in step 1 were added, the air in the autoclave was replaced with N2 five times, and then H2 was introduced to 6.2MPa. The temperature was raised to 200°C while stirring, and the reaction pressure was controlled to rise to a maximum of 8.5MPa. The hydrogenolysis reaction was carried out for 5 hours. After the reaction is completed, the reaction mixture is filtered and the filter cake is rinsed with ethanol. The solid is ultrasonically washed with 5% hydrochloric acid, 5% sodium hydroxide, deionized water, ethanol, and deionized water in sequence, dried at 80°C for 12 hours, ground, and passed through a 40-mesh sieve. The resulting material is calcined at 350°C in a muffle furnace for 5 hours. The catalyst is regenerated and applied. The filtrate is decompressed and the solvent is removed by vacuum distillation. The 166-168°C / 4mmHg fraction is collected to obtain 18.82 g of a white solid. GC analysis shows that the purity is 99.51% and the yield is 93.03%.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low-cost composite metal catalyst, characterized in that: The composite catalyst is a CuO / ZnO / Al2O3 composite metal catalyst, wherein the molar ratio of CuO, ZnO and Al2O3 is 6-4:3-4:0.5-1; the composite catalyst is prepared by adding carbonate to a mixed salt solution of copper salt, zinc salt and aluminum salt for co-precipitation, grinding the filter cake and then high-temperature calcination.
2. The composite metal catalyst according to claim 1, characterized in that The preparation method of the composite metal catalyst is as follows: preparing a mixed salt solution containing copper salt, zinc salt and aluminum salt, gradually adding a carbonate solution to the mixed salt solution, wherein the ratio of the molar amount of the carbonate to the total molar amount of the copper ion, the zinc ion and the aluminum ion is 1 to 1.1:1; During the dropping process, the reaction system is continuously stirred and maintained at a pH of 7-7.4; the temperature is 70-75°C; after the dropping is completed, a suspension is obtained, the suspension is heated to 80-85°C, aged for 30-40 minutes, and then the precipitate is filtered out, and the filter cake is washed with deionized water; the washed filter cake is dried, ground, and passed through a 40-60 mesh sieve to obtain a powder, and the powder is roasted at 350-550°C for 4-6 hours to obtain the composite metal catalyst.
3. The composite metal catalyst according to claim 2, characterized in that During the dropping process, the reaction system was continuously stirred and the pH value was maintained at 7. The temperature was 70° C. After the dropping was completed, a suspension was obtained, the suspension was heated to 80° C., aged for 30 min, and then the precipitate was filtered out and the filter cake was washed with deionized water. The washed filter cake was dried, ground, and passed through a 40-mesh sieve to obtain a powder, which was calcined at 350° C. for 5 h to obtain the composite metal catalyst.
4. The composite metal catalyst according to claim 2, characterized in that The copper salt, zinc salt and aluminum salt are copper nitrate, zinc nitrate and aluminum nitrate respectively; the preparation process is: according to the stoichiometric ratio of each element of the composite metal catalyst, Cu(NO3)2.3H2O, Zn(NO3)2.6H2O, Al(NO3)3.9H2O are weighed, and dissolved in deionized water to prepare the mixed salt water solution.
5. The composite metal catalyst according to claim 2, characterized in that The carbonate is sodium carbonate.
6. An industrial synthesis method of 1,12-dodecanediol, characterized in that: It includes: (1) putting dimethyl 1,12-dodecanedioate into a reaction kettle containing ethanol, adding the composite metal catalyst according to any one of claims 1 to 5 in an amount of 4.5 to 6% by mass of the dimethyl 1,12-dodecanedioate, and dispersing the mixture uniformly; (2) introducing nitrogen or argon to evacuate and deoxygenate the reactor, then introducing hydrogen to make the pressure in the reactor reach 6.0-6.2 MPa, raising the temperature to 200-250° C. under stirring to carry out hydrogenolysis reaction, continuously introducing hydrogen during the reaction, controlling the reaction pressure to rise to a maximum of 8.3 MPa-12 MPa, and completing the reaction for 4.5-6 hours; (3) After the reaction is completed, the reaction mixture is filtered and the filter cake is rinsed with ethanol. The solid obtained is the recovered catalyst. The filtrate obtained by filtration is evaporated under reduced pressure to remove the solvent, and the filtrate is distilled under reduced pressure to collect the 166-168°C / 4 mmHg fraction to obtain a white solid, which is 1,12-dodecanediol.
7. The industrial synthesis method according to claim 6, characterized in that The method also includes regenerating the recovered catalyst, and the treatment process includes: washing the obtained solid with dilute hydrochloric acid, dilute sodium hydroxide solution, deionized water, ethanol, and deionized water ultrasonically in sequence, drying after washing, grinding, and passing through a 40-60 mesh sieve to obtain a powder, and roasting the powder at 350-550° C. for 4-6 hours to complete the regeneration of the catalyst.
8. The industrial synthesis method according to claim 7, characterized in that: The regenerated catalyst was used for the synthesis of the next batch of 1,12-dodecanediol.
9. The industrial synthesis method according to claim 7, characterized in that: The process of regenerating the recovered catalyst includes: washing the obtained solid with 5% hydrochloric acid, 5% sodium hydroxide solution, deionized water, ethanol, and deionized water ultrasonically in sequence, drying after washing, grinding, and passing through a 40-mesh sieve to obtain a powder, and calcining the powder at 350°C for 5 hours to complete the regeneration of the catalyst.
Citation Information
Patent Citations
Production method of alpha,omega-long carbon chain n-dihydric alcohol
CN103449971A
Cited By
Methanol catalyst forming method, methanol catalyst and application
CN120502327A
Preparation method of 1, 12-dodecanediol
CN120904013A